Sustainable Development Assessment of Zinc Oxide Production focused on Agribusiness - Isabelle Monfrinatti Macarrão; Júlio Cesar Dutra (The Journal of Engineering and Exact Sciences, 2020)
Agribusiness sectors have evolved to a highly diversified level, the fertilizer being their main interest. These products are composed of macronutrients and micro ones essential to life. Zinc is an essential micronutrient, and it is present in fertilizers as zinc oxide. The present work is concerned with assessing, from the sustainable development viewpoint, the entire chain of production and transportation of zinc oxide. It is intended to establish an ecological audit of ZnO by the CES EduPack® software in six different scenarios. The scenario composed only of recycled material for furnace feeding was the one that spent the least energy of all and had the lowest carbon footprint. However, a scenario composed only of pure zinc was the one that spent more energy and had the highest carbon footprint. Transport was the highest consumer of energy and carbon footprint in all scenarios.